2011
DOI: 10.1534/genetics.111.133967
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Opaque7 Encodes an Acyl-Activating Enzyme-Like Protein That Affects Storage Protein Synthesis in Maize Endosperm

Abstract: In maize, a series of seed mutants with starchy endosperm could increase the lysine content by decreased amount of zeins, the main storage proteins in endosperm. Cloning and characterization of these mutants could reveal regulatory mechanisms for zeins accumulation in maize endosperm. Opaque7 (o7) is a classic maize starchy endosperm mutant with large effects on zeins accumulation and high lysine content. In this study, the O7 gene was cloned by map-based cloning and confirmed by transgenic functional compleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(105 citation statements)
references
References 55 publications
(72 reference statements)
3
98
0
1
Order By: Relevance
“…It is believed that zein protein bodies play an important role in the vitreous endosperm phenotype at kernel maturity. Several maize opaque mutants, such as o2, o7, fl2, De-B30, and Mc (Schmidt et al, 1990;Gillikin et al, 1997;Kim et al 2004Kim et al , 2006Wang et al, 2011b), result in quantitative or qualitative alternations in zein accumulation. Consistent with a previous report (Hunter et al, 2002), we found that all the o1 alleles result in no significant changes in zein or nonzein proteins at maturity (Table 1; see Supplemental Figure 1 online).…”
Section: O1 Affects Zein Protein Body Biogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…It is believed that zein protein bodies play an important role in the vitreous endosperm phenotype at kernel maturity. Several maize opaque mutants, such as o2, o7, fl2, De-B30, and Mc (Schmidt et al, 1990;Gillikin et al, 1997;Kim et al 2004Kim et al , 2006Wang et al, 2011b), result in quantitative or qualitative alternations in zein accumulation. Consistent with a previous report (Hunter et al, 2002), we found that all the o1 alleles result in no significant changes in zein or nonzein proteins at maturity (Table 1; see Supplemental Figure 1 online).…”
Section: O1 Affects Zein Protein Body Biogenesismentioning
confidence: 99%
“…At least 18 of these have been positioned on the genetic map (Gibbon and Larkins, 2005). So far, only seven genes corresponding to these mutants have been cloned, including opaque2 (o2), o5, o7, floury1 (fl1), fl2, Mucronate (Mc), and Defective endosperm B30 (De-B30) (Schmidt et al, 1990;Coleman et al, 1997;Kim et al, 2004Kim et al, , 2006Holding et al, 2007;Miclaus et al, 2011;Myers et al, 2011;Wang et al, 2011b). The majority of these mutants result from defects in zein protein synthesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The O7 gene was recently cloned by two different groups, using a combination of mapbased cloning and transposon tagging and confirmed by transgenic functional complementation Wang et al, 2011). Moreover, these last workers via sequence analysis indicated that the O7 gene showed similarities with members of the larger family of acyl-CoA synthetase-like genes (ACS), although its exact enzymatic activity is uncertain.…”
Section: Molecular Basesmentioning
confidence: 99%
“…Note added in proof: See Wang et al 2011Wang et al (pp. 1281Wang et al -1295) in this issue, for a related work.…”
Section: Acknowledgmentsmentioning
confidence: 99%